Influence of the RuO2 layer thickness on the physical and electrochemical properties of anodes synthesized by the ionic liquid method - Dória, Aline R. (2020)
The use of ionic liquids as solvents to prepare mixed metal oxide (MMO) anodes has proven to be a very promising alternative synthesis route. However, little attention has been dedicated to assessing the effect of the coating thickness on their activity and service life, and no detailed study of the thickness of anodes made using ionic liquids has been conducted to date. Here we studied the influence of the ruthenium oxides film thickness (8.2, 13.7, and 16.5 μm) on the physical, electrochemical, and electrocatalytic properties of Ti/RuO2 anodes. The electrodes were prepared using the 2-hydroxyethyl ammonium acetate (2HEAA) ionic liquid as the solvent of the precursor solutions. The properties of these anodes were compared with the RuO2-based commercial anode provided by De Nora® (17.7 μm of thickness). The increase in RuO2 layer thickness from 8.2 μm to 13.7 μm, and then to 16.5 μm decreases the voltammetric anode charge and increases their charge transfer resistance from 11.2 Ω to 28.2 Ω, and then to 52.7 Ω, respectively. Deactivation of the anodes was investigated by accelerated lifetime tests in H2SO4 and NaCl solutions. In acidic media, the anodes with a higher thickness (13.7 μm and 16.5 μm) presented longer service lifetimes, respectively, 1.5 and 1.4 higher than the electrode with 8.2 μm. In NaCl medium, a higher thickness improves the service life significantly. The anode with 16.5 μm of thickness has a service life up to 48.6 times higher than the anode with 8.2 μm. All anodes, including the commercial one, presented high catalytic efficiency towards the electrochemical degradation of Reactive Black 5 dye. Within only 30 min of electrochemical treatment, all anodes removed more than 94% of color. It is shown that the use of anodes with low coating thicknesses is more favorable due to reduced time and energy costs of the synthesis process while maintaining a high degradation efficiency of the dye.